Human Exposure to Pollutants via Dermal Absorption and Inhalation - Lazaridis, Mihalis; Colbeck, Ian.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2010)
The human body is exposed to pollution on a daily basis via dermal exposure and inhalation. This book reviews the information necessary to address the steps in exposure assessment relevant to air pollution. The aim is to identify available information including data sources and models, and show that an integrated multi-route exposure model can be built, validated and used as part of an air quality management process. Many epidemiological studies have focused on inhalation exposure. Whilst this is appropriate for many substances, failure to consider the importance of exposure and uptake of material deposited on the skin may lead to an over/underestimation of the risk. Hence dermal exposure is also considered. Drinking water contamination by disinfection by-products is also discussed. Written by leading experts in the field, this book provides a comprehensive review of ambient particulate matter and will be of interest to graduate students, researchers and policymakers involved in air quality management, environmental health and related disciplines, as well as environmental consultants and ventilation engineers.
Environmental Levels -- Indoor Air Pollution -- Chemical Reactions Among Indoor Pollutants -- Personal Exposure Measurements -- Health Effects of Air Pollutants -- Inhalation Dosimetry Modelling -- Dermal Absorption Modelling -- Micro-environmental Modelling -- Air Quality Management and Personal Exposure.
Keywords: Environment; Medicine; Environmental health; Pollution; Air pollution; Water pollution; Environment; Pollution, general; Waste Water Technology / Water Pollution Control / Water Management / Aquatic Pollution; Medicine/Public Health, general; Environment, general; Atmospheric Protection/Air Quality Control/Air Pollution; Environmental Health; Electronic books